L’aggressione e l'incontro: risonanza e critica della modernità in Hartmut Rosa - Andrea M. Maccarini (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
Hartmut Rosa has grown to international celebrity thanks to his theory of social acceleration as a new interpretation of modernity, linked with the imperative of growth and the idea of alienation. His recent work has revolved around the concept of resonance, and although this has raised significant interest, its positioning within contemporary sociological theory still needs further study. This article starts situating the notion of resonance in the wider context of Rosa’s theoretical enterprise (section 1). The following section outlines the key concepts and the main argument comprising his theory of resonance, and briefly examines some specific challenges to resonance emerging in the current predicament (section 2). Finally, the article ends by connecting idea of resonance with a few pivotal themes in contemporary sociological theory, with a special focus on Margaret Archer’s morphogenetic approach and her theory of the Self and personal reflexivity (section 3). The core thesis of the article is that the notion of resonance still calls for better understanding within social theory, precisely because of the specific type of critique of modernity inherent in such a concept.